Generalized Sum of Fuzzy Subgroup and Î±-cut Subgroup - Waly Freh, Daher; Shany Hassan, Alia (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper we study some results of the generalized sum of a fuzzy subgroup and Î±-cut subgroup ,we define a Î±-cut subset and Î±-cut subgroup, and then .We study some of their properties.